Contrasting snus and NRT as methods to quit smoking. an observational study - Scheffels Janne; Lund Karl E; McNeill Ann (BMC, 2012)
Abstract Background Snus is considerably less hazardous to health than cigarettes. Recent data from Scandinavia have indicated that many smokers use snus as a method for quitting smoking. Methods Data from five repeated cross-sectional surveys of Norwegian men and women aged 16-74 were pooled (N = 6 262). Respondents were asked about current and former smoking and snus use. Former daily smokers (N = 1219) and current daily smokers who had tried to quit at least once (N = 1118) were asked about the method they had used at their latest quit attempt and how many quit attempts they had made. Former smokers were also requested to report what year they had made their final quit attempt. Results Snus was the most common method used for quitting smoking among men, while NRT was most often used among women. Stratifying the data according to year of quitting smoking (1945-2007) indicated a significant increase in use of the methods for quitting asked about over time. Among men, this was largely due to an increase in the use of snus. Among male quitters under the age of 45 years, 45.8% of those who had used snus on their last attempt to quit were current non-smokers (OR = 1.61, CI 1.04-2.29), while 26,3% of those who had used NRT were current non-smokers. 59.6% of successful quitters and 19.5% of unsuccessful quitters who had used snus as a method for quitting smoking had continued to use snus on a daily basis after quitting. Conclusion Norwegian men frequently use snus as a method for quitting smoking whereas women are more likely to use NRT. The findings indicate that switching to snus can be an effective method for quitting smoking.